Piety, Social Pressure, and Riya’: Religious Practices of Yogyakarta Urban Muslim Youth in Digital Media - Achfandhy, Mochammad Irfan; Rohmatulloh, Dawam Multazamy (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2024)
This article examines the relationship between piety, social pressure, and riya’ among urban Muslim youth in Yogyakarta who use social media to express religiousity, and the way the youth negotiate to deal with the contradiction between displayed piousness and religious norms. Employing a phenomenological approach this article explore the negotiation of ambiguity among urban Muslim youth, in particular the urban students actively involved in lecture series branded "Ngaji Filsafat" conducted by Dr. Fahruddin Faiz. This article argue that not only digital media provide space for youth to express their piety, it also offer bigger social pressure to gain social validation for their (digital) existence, in the form of likes and followers, for instance. The social pressure increases ethical ambiguity, where expressions of online piety can be considered as violating a moral principle of religiosity, namely riya’. Finally, this article contributes to debates on the intersection of religion and media, especially on the aspect of individual negotiation space in responding to biases and dilemmas arising from the hybridity of the two.